2016
DOI: 10.1364/oe.24.008895
|View full text |Cite
|
Sign up to set email alerts
|

Multi-channel control for microring weight banks

Abstract: We demonstrate 4-channel, 2GHz weighted addition in a silicon microring filter bank. Accurate analog weight control becomes more difficult with increasing number of channels, N, as feedback approaches become impractical and brute force feedforward approaches take O(2N) calibration measurements in the presence of inter-channel dependence. We introduce model-based calibration techniques for thermal cross-talk and cross-gain saturation, which result in a scalable O(N) calibration routine and 3.8 bit feedforward w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…Previous work on microring (MRR) weight banks have established a correspondence between weighted addition operations and integrated photonic filters. In reference to the operation, MRR weight bank scalability 34 and accuracy 35 metrics can be defined, but MRR weight banks have not been demonstrated within a network.
Figure 1 Broadcast-and-weight protocol and experiment.
…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on microring (MRR) weight banks have established a correspondence between weighted addition operations and integrated photonic filters. In reference to the operation, MRR weight bank scalability 34 and accuracy 35 metrics can be defined, but MRR weight banks have not been demonstrated within a network.
Figure 1 Broadcast-and-weight protocol and experiment.
…”
Section: Introductionmentioning
confidence: 99%
“…Microring weights are controlled using the feedforward approach developed in Ref. [47]. First, an optical spectrum analyzer (OSA) is used to independently track MRR resonances onto their corresponding WDM signal wavelengths.…”
Section: B Silicon Microring Weight Banksmentioning
confidence: 99%
“…Ref. [113] described a method for fitting parameters with O(N) spectral and oscilloscope measurements, where N is the number of MRRs. As an example, whereas an interpolation-only approach with 20 points resolution would require 20 4 = 160,000 calibration measurements, the presented calibration routine takes roughly 4 × [10(heater) + 20(filter) + 4(amplifier)] = 136 total calibration measurements.…”
Section: Multichannel Control Accuracy and Precisionmentioning
confidence: 99%
“…In Ref. [113], it was concluded that ADC resolution, sensitivized by biasing conditions, limited the attainable weight accuracy. Controller accuracy is expected to improve by reducing the mismatch between tuning range of interest and driver range.…”
Section: Weight Bank Channel Limitsmentioning
confidence: 99%